Design of a power profiler for domestic load research analysis - Stowe, Grant (Department of Electrical Engineering, 2016)
This dissertation presents the development of a proof-of-concept measurement instrument to satisfy the requirements of the University of Cape Town's Load Research Group. The new instrument needed to make use of current technologies to cost-effectively measure multiple residential households and provide remote communications capabilities for reliable remote data retrieval. Measurement of three-phase 4-wire configurations was necessary as well as the ability to create second-based profiles of consumer voltage, current and active, reactive and apparent powers for load identification purposes. The main components of a measurement system were identified and prototype development was split into two stages: component integration testing and final product integration. The product was called the Power Profiler and two early prototypes were developed to test the main measurement and processing components and mechanical integration to create a compact versatile test instrument. Energy measurement ICs were used instead of discrete sampling of voltage and current to improve accuracy and allow the use of a low- cost and easy to program digital signal controller for measurement processing and storage. Several communication options were incorporated into the Power Profiler including remote GSM and local USB and Bluetooth communication. The third prototype was subjected to full calibration testing with a Chauvin Arnoux power quality analyzer used as the reference meter. The Power Profiler proved to be a high accuracy instrument with a typical inaccuracy of 0.4% for RMS voltage (over a 20:1 range), 0% for RMS current, 1.1% for active power, 0.3% for reactive power and 0.1% apparent power versus the reference meter. To validate the Power Profiler measurement functionality it was connected to a residential household in conjunction with the reference meter and 4 hours of measurement data was captured for comparison. After a successful validation the Power Profiler was then left to capture another 43 hours of measurement data using a 5-second, 10-minute and 2-hour measurement profile. This data was then analyzed to see if non-intrusive load discrimination could be performed. From the measurement and validation data several common household appliances were identified including the refrigerator, geyser, kettle, microwave and washing machine. The Power Profiler stores not only the average values measured between recording intervals but the maximum and minimum levels as well. This data proved very valuable for the detection of voltage dips and swells that would otherwise have gone unreported by a conventional power meter. The maximum statistic also effectively showed the startup current of motor-based appliances such as the refrigerator and washing machine which greatly assisted with load discrimination. The embedded software for the Power Profiler was split into several software tasks to simplify code maintenance and future development. A C# PC Control and Configuration application was developed to automate calibration as far as possible, and to allow an operator to configure and upload measurement data from the Power Profiler. Extensive use of object-oriented programming techniques was made to allow the reuse of the interface and control software in future applications by other developers. Remote communications capabilities were demonstrated over GSM GPRS connections to allow the retrieval of measurement data from field-deployed Power Profilers. The ability of the Power Profiler to simultaneously record second-, minute- and hour-based profiles and to allow the operator to decide which of this measured data to upload is highly effective in managing remote communication bandwidth and reducing overall operating cost of the system. The Power Profiler product proved to be a cost-effective replacement to the currently used logger and offered more channels with higher resolution measurement and profiling capabilities in a compact instrument. Remote communication capabilities reduces the overall operating cost of the system and simplified measurement retrieval. The ability to easily custom-develop software for both the Power Profiler and PC-based applications made it a flexible instrument valuable for research-orientated applications.